The Effectiveness of Cognitive Behavioral Group Psychotherapy For Obsessive-Compulsive Disorder - Turkcapar, Mehmet Hakan; Safak, Yasir; Karadere, Mehmet Emrah; Ozdel, Kadir; Ozcan, Turkan; Kuru, Erkan; Yucens, Bengu (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2014)
Objective: The aim of this study was to determine the effectiveness of cognitive behavioral group therapy (CBGT) in the treatment of the obsessive-compulsive disorder (OCD). Materials and Methods: The study included 82 patients diagnosed as OCD according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR). In all, 37 patients that had their diagnosis confirmed via the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) and agreed to participate were provided group therapy as 14 weekly 90-120-min sessions. The Yale-Brown Obsessive Compulsive Scale (Y-BOCS), Yale-Brown Obsessive Compulsive Scale-Symptom Checklist (Y-BOCS-SC), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were administered to the patients prior to group therapy (baseline) and again after sessions 2, 5, 8, 12, and 14. Results: In all, 8 patients dropped out of the study for various reasons and 29 completed the group therapy. There were significant reductions in BAI, BDI, and Y-BOCS scores in the patients that completed the group therapy. Additionally, BM, BDI, and Y-BOCS score did not differ according to age, gender, or level of education. Conclusions: CBGT was associated with significant improvement in OCD symptoms. Neither demographic characteristics (age, gender, and education level), nor clinical characteristics (disease duration, type of obsession, compulsion type, treatment history, and comorbidity pattern) had an effect on treatment outcome. In light of these findings, we think CBGT is an effective option for the treatment of OCD.
Keywords: Obsessive-compulsive disorder; cognitive therapy; behavior therapy; psychotherapy, group